Criteria for Determining Subuh Prayer Time by the Wahdah Islamiyah Jamaat: Socio-Religious Implications - Muh Arif Royyani; Nurul Wasilah Wahidin; Nur Hijriah; Multazam; Abdulaziz Kalupae (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2025)
The implementation of prayer and fasting in Indonesia is diverse because each Islamic organisation has a variety of criteria for the height of the angle of the sun, which varies. Wahdah Islamiyah, as one of the Islamic mass organisations, sets the initial criteria for dawn prayer time at -17.5º, while the initial guideline criteria for subuh prayer time of the Ministry of Religious Affairs is -20º. This study analyses the basis for determining the criteria for the beginning of the Wahdah Islamiyah subuh prayer time, along with socio-religious implications in society through shari’i, astronomical, and sociological approaches. Data are collected through interviews and documentation. The study shows the basis for determining the criteria of Wahdah Islamiyah using hisab, considering astronomical aspects, waṣatiyyah (middle) aspects, and sociological factors. The socio-religious implications of the -17.5º criterion can still be applied in subuh prayers because it is still within the grace period. It cannot be used for fasting implementation in Makassar City, Indonesia, but only within the scope of Wahdah Islamiyah, as it exceeds the limits as referenced in the calendar published by the Ministry of Religious Affairs. This study recommends establishing dialogue between stakeholders on the societal implications of differing prayer and imsak time criteria. It also emphasises the need for integrating scientific and religious approaches in determining worship times within the global Muslim community.